Physically Unclonable Functions From Basic Design Principles to Advanced Hardware Security Applications - Halak, Basel (Springer International Publishing, 2018)
This book discusses the design principles of physically unclonable functions (PUFs) and how these can be employed in hardware-based security applications, in particular, the book: Provides readers with a comprehensive overview of security threats on embedded systems and existing countermeasures; Includes an intensive tutorial on how to design and evaluate physically unclonable functions, supported by circuit diagrams and exemplar hardware implementations; Discusses the reliability challenges facing PUF technology and explains in details the state of the art mitigation approaches adopted, including those based on error correction codes and/or pre-processing techniques; Gives a comprehensive tutorial on the security threats facing PUF technology, including modelling attacks using machine learning algorithms, side channel analysis, and physical attacks. It also outlines possible countermeasures and defence mechanisms; Explains in detailed the practical applications of PUF technology, these include secure cryptographic key generation and storage, hardware-assisted security protocols, low cost secure sensors, anti-counterfeit integrated circuits and anti-tamper hardware. This book has many features that make it a unique source for students, engineers and educators, including more than 80 problems and worked exercises, in addition to, approximately 200 references, which give extensive direction for further reading. .